Transborder Movements and Relations in the Slovakian–Hungarian Border Regions - Hardi, Tamás (Discussion Papers, 2012)
The present study features the findings of a research conducted in the Slovak-Hungarian border region, the longest border section of Hungary, a functional area, home to approximately 2 million people. The research was implemented in the framework of the Hungary-Slovakia-Ukraine Neighbourhood Programme. The aim of the research was to study the everyday movements of the popula¬tion living in the border region. We assumed that the accession to the Union and the Schengen Zone would promote the integration of the border region, the devel¬opment and expansion of the cross-border interactions, and in the end the birth of cross-border regions in the areas in good positions. The occasionally “cool” relationship of the two states cannot be felt in the micro-level relations, in the economically more advanced areas of the borders we can see the first steps of the birth of single border regions. The private sector is ahead of the official relations. A part of the inhabitants and the economic sector “use” the other side of the border in their everyday lives. The separating role of the “mental border” is less of a problem here than in some other European border areas. There are still many obstacles to the complete integration. The national systems (education, health care, public administration, bureaucracy etc.) still have difficulties in handling the natural processes of cross-border areas.